INVESTIGATION OF THE PROPERTIES OF THE SUSPENSIONS FOR NON-STICK COATINGS FOR FOUNDRY - T. Gil’manshina; S. Lytkina; T. Bogdanova; S. Hudonogov; A. Kosovich; E. Partyko (Литьë и металлургия)
The research aimed at figuring out dependence of the technological properties (density, thickness of the coating, reduced strength and sedimentation stability) of the suspensions for nonstick coatings on the for activation time powder quartz graphite filler. It is shown that with increasing activation time to 10 minutes all the basic properties of graphite suspension powder quartz were improved. The paper presents the results of comparative studies of technological properties of suspensions of activated graphite oxide compositions prepared on the basis of activated aluminum oxide and periclase. The resulting suspension may be recommended for cast iron and non-ferrous castings.